FINANCIAL MANAGEMENT ANALYSIS OF MINHAJUL HAQ ISLAMIC BOARDING SCHOOL IN PURWAKARTA - Rohman Pranoto; Isrun Abdurahman; Cahyudi Prima; Rizaldy Alpiansyah; Irfan Alkhotiri (Sekolah Tinggi Agama Islam Minhajul Haq, 2026)
The aim of this research is to analyze the extent of financial management that occurs at the Minhajul Haq Kiarapedes Purwakarta Islamic boarding school, what obstacles arise in this regard and what efforts must be made in order to achieve ideal financial management. In this research, the method used is descriptive research and is a case study which is studied quantitatively. In this case, the financial condition of the Minhajul Haq Islamic boarding school is explained, while quantitatively the strength of effectiveness and efficiency of financial management of the Minhajul Haq Islamic Boarding School is calculated. The unit of analysis in this research is the financial management of the Minhajul Haq Islamic boarding school from 2020 to 2022. The results of this research show that the calculation of the formulation of the level of effectiveness of Islamic boarding school financial management from 2020 to 2022 fluctuates with an average effectiveness level of 92.09%. . This shows that the financial management of the Minhajul Haq Islamic Boarding School is at an effective management level. Meanwhile, the results of the analysis of financial management efficiency show that the calculation of the overall efficiency level formulation is an average of 107.14%. This shows that the level of efficiency is still low because the results are more than 100%. Thus, the Minhajul Haq Islamic Boarding School is still wasteful in using its budget. Apart from that, it also explains the principles of financial management such as transparency, accountability as well as obstacles in supporting ideal financial management and efforts to achieve them. Keywords: Financial Management, Effectiveness, Efficiency